Comparison of [18 F]fluorocholine and [18 F]fluorodeoxyglucose for positron emission tomography of androgen dependent and androgen independent prostate cancer - Price, David T; Coleman, R Edward; Liao, Ray P; Robertson, Cary N; Polascik, Thomas J; DeGrado, Timothy R (The Journal of urology, 2002)
Positron emission tomography (PET) imaging is used for the metabolic evaluation of cancer. [18F]fluorodeoxyglucose (FDG) is commonly used as a radiotracer but its low cellular uptake rate in prostate cancer limits its usefulness. We evaluated the novel choline analog [18F]fluorocholine (FCH) for detecting androgen dependent and androgen independent prostate cancer, and its metastases. The cellular uptake of FCH and FDG was compared in cultured prostate cancer cells (LNCaP and PC-3). FCH and FDG were injected into nude mice xenografts (CWR-22 and PC-3) and radiotracer uptake in various organs were evaluated. Patients with androgen dependent (9) and independent (9) prostate cancer were studied by FCH and FDG PET. FCH uptake was 849% and 60% greater than FDG uptake in androgen dependent (LNCaP) and independent (PC-3) cells, respectively. The addition of hemicholinium-3 (5 mM.) 30 minutes before radiotracer administration inhibited FCH uptake by 79% and 70% in LNCaP and PC-3 cells, respectively, whereas FDG uptake was not significantly affected. Although nude mice xenografts showed that FDG uptake was equal to or greater than FCH uptake, clinical imaging in patients demonstrated 2 to 4-fold higher uptake of FCH in those with androgen and androgen independent prostate carcinoma (p <0.001). More lesions were detected by FCH than by FDG in primary tumors, osseous metastases and soft tissue metastases. In vitro data demonstrated greater FCH than FDG uptake in androgen dependent (LNCaP) and androgen independent (PC-3) prostate cancer cells. Although the murine xenograft data showed greater accumulation of FDG than FCH in PC-3 tumors, PET in humans showed that FCH was better than FDG for detecting primary and metastatic prostate cancer. Overall the data from this study suggest that FCH is preferable to FDG for PET of prostate carcinoma and support the need for future validation studies in a larger number of subjects.